Placement of C1 Lateral Mass Screw—Alternative Technique: 2‐Dimensional Operative Video. Issue 3 (September 2020) - Jha, Tushar R.; Dietz, Nicholas; Dowlati, Ehsan; Sandhu, Faheem
Abstract : N/A: This operative video demonstrates a C1 lateral mass instrumentation technique that is an alternative to the traditional Goel and Harms techniques.1, 2 The advantages of the alternative technique include minimized blood loss from the rich venous plexus surrounding the C2 dorsal root ganglia (DRG), avoidance and preservation of the C2 DRG, and placement of a robust fully threaded screw without risking neuralgia. These are discussed in detail and presented through a case of atlantoaxial instability. Patient's consent was obtained for creating this surgical video. The patient is a 50‐yr‐old woman with a 17‐yr history of rheumatoid arthritis. She presented with 1 yr of neck pain that failed conservative measures. Flexion‐extension radiographs demonstrated an atlantodental index (ADI) that reduced from 7 mm on flexion to 0 mm on extension. The patient underwent a C1‐C2 posterior instrumented fusion using the alternative technique of C1 lateral mass instrumentation.2 The steps of this technique are explained in great detail through a microsurgical video. The patient's postoperative course was uneventful. Postoperative radiographs and computed tomography (CT) scan demonstrated reduction of ADI and well‐placed instrumentation and fusion construct. Her neck pain was completely resolved by 3 mo following surgical stabilization. In the senior author's experience with placing over 120 C1 lateral mass screws with this alternative technique, there have been no instances of vascular injury, sacrifice of C2 DRG, or instrumentation failure. The alternative technique for placement of C1 lateral mass screw is safe, efficient, and holds certain advantages in comparison to the traditionally described method. Images within the video have been reproduced from AOSpine section of the AO Surgery Reference, www.aosurgery.org, with permission from AO Surgery. Copyright by AOSpine International, Switzerland; and reprinted from World Neurosurgery, 78(1‐2), Kang MM et al, C2 Nerve Root Sectioning in Posterior C1‐2 Instrumented Fusions, 170‐177, Copyright 2012, with permission from Elsevier.